Analysis Of The Effect Of Perceived Usefulness, Trust And Digital Capability On Technology Adoption In The Learning Process: Penelitian - Riyanti, Apriani; Ismunandar, Arif; Pramono, Susatyo Adhi; Hendratni, Tyahya Whisnu; Syafrullah, Haidir; Arsyad, Muhammad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The research was aimed at understanding how the perception of usefulness, trust, and digital capability affects the level of technology adoption in the learning process in educational institutions. The research utilized a quantitative survey method with 150 purposively selected respondents. The respondents were teachers from five big cities in Indonesia who have been using digital technology in their teaching activities for at least one year. Multiple linear regression was used for data analysis, following the performance of normality, heteroscedasticity, and multicollinearity tests to confirm the feasibility. The findings indicate that the three variables of perceived usefulness, trust, and digital capability not only individually but also as a whole are a major determinant of technology adoption in learning. These findings add to the existing technology acceptance literature in education and have also the potential to be an issue for the school administrators in facilitating the use of technology to the fullest extent. One way of doing this can be through the promotion of technology benefits, the building of trust in the digital systems, and the provision of digital capacity to the teachers and the learners so that technology-assisted learning becomes more efficient and can easily continue.